Epistemic Beliefs Moderate Mediations Among Attitudes, Prior Misconceptions, and Conceptual Change - Vivian, James; Muis, Krista Renee (Advances in Social Sciences Research Journal, 2020)
We investigated the mediating and moderating roles of attitudes and epistemic beliefs in conceptual change during learning about genetically modified foods (GMFs). One hundred twenty undergraduate students participated. To measure misconceptions about GMFs, students first completed a prior knowledge test. Students then completed self-report inventories to measure their attitudes and topic-specific epistemic beliefs regarding GMFs. Students were then randomly assigned to read a refutation or expository text about GMFs. Following reading, students completed a test to assess conceptual change. Results of a repeated measures ANOVA revealed participants who read a refutation text changed more misconceptions at post-test than participants who read an expository text. A moderation mediation analysis revealed attitudes toward GMFs significantly mediated the relationship between prior misconceptions and conceptual change, and that this relationship was moderated by learners’ beliefs regarding the source and justification of GMFs knowledge. Theoretical and educational implications are discussed.